The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1186/s12881-019-0745-7
|View full text |Cite
|
Sign up to set email alerts
|

Novel ANKRD11 gene mutation in an individual with a mild phenotype of KBG syndrome associated to a GEFS+ phenotypic spectrum: a case report

Abstract: BackgroundKBG syndrome is a very rare autosomal dominant disorder, characterized by macrodontia, distinctive craniofacial findings, skeletal findings, post-natal short stature, and developmental delays, sometimes associated with seizures and EEG abnormalities. So far, there have been over 100 cases of KBG syndrome reported.Case presentationHere, we describe two sisters of a non-consanguineous family, both presenting generalized epilepsy with febrile seizures (GEFS+), and one with a more complex phenotype assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 24 publications
(32 reference statements)
0
18
0
Order By: Relevance
“…Pathogenic ANKRD11 mutations in patients presenting with an additional genetic anomaly have been reported, including a KMT2D mutation of Kabuki syndrome (Tunovic, Barkovich, Sherr, & Slavotinek, ), a de novo deletion of chromosome 9q (Xu et al, ), mutations in FLG (Ichthyosis vulgaris, MIM 146700), ARID1B (Coffin‐Siris syndrome, MIM #135900) and SLC6A 1 (Myoclonic‐atonic epilepsy, MIM #616421) in three different patients (Posey et al, ), a generalized epilepsy with febrile seizures due to SCN9A mutation (Alves et al, ). The use of exome sequencing will probably lead to the identification of additional associations, as shown by the study about co‐occurrences by Posey et al ().…”
Section: Discussionmentioning
confidence: 99%
“…Pathogenic ANKRD11 mutations in patients presenting with an additional genetic anomaly have been reported, including a KMT2D mutation of Kabuki syndrome (Tunovic, Barkovich, Sherr, & Slavotinek, ), a de novo deletion of chromosome 9q (Xu et al, ), mutations in FLG (Ichthyosis vulgaris, MIM 146700), ARID1B (Coffin‐Siris syndrome, MIM #135900) and SLC6A 1 (Myoclonic‐atonic epilepsy, MIM #616421) in three different patients (Posey et al, ), a generalized epilepsy with febrile seizures due to SCN9A mutation (Alves et al, ). The use of exome sequencing will probably lead to the identification of additional associations, as shown by the study about co‐occurrences by Posey et al ().…”
Section: Discussionmentioning
confidence: 99%
“…The first and second frequent phenotypes are febrile seizures, where generalized tonic-clonic seizures (GTCS) with fever occur between 3 months and 6 years, and febrile seizures plus (FS+), in which attacks with fever extend beyond 6 years or afebrile GTCS occur, respectively. The other phenotypes include FS/ FS+ with absence, myoclonic, atonic, or focal seizures [11]. In our study, the proband experienced FS and FS+ with absence while his father and aunt only had febrile seizures, probably due to the incomplete penetrance and/or the phenotypic heterogeneity.…”
Section: Discussionmentioning
confidence: 53%
“…Cen et al reported a small pedigree diagnosed as GEFS+ with a heterozygous mutation (Q10R) in SCN9A gene without SCN1A mutation [4]. In 2019, a heterozygous mutation in the SCN9A gene, p.(Lys655Arg), in two sisters from a nonconsanguineous family who presented GEFS+ was detected [11]. Actually, SCN9A variant is often mentioned as a genetic modifier in SCN1A mutation-associated epilepsy.…”
Section: Discussionmentioning
confidence: 99%
“…Since then, we never used that term again and encourage all physicians to do the same. The widespread insensibility concerning the use of the term ‘dwarf’ or similar40–49 underscores the present need of finally eliminating such terms from the medical lexicon. To this regard, it is relevant to quote at this time Dr David W Smith, the father of modern dysmorphology.…”
Section: Global Health Problem Analysismentioning
confidence: 99%